1999
DOI: 10.1007/s002620050543
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of a HER2/neu bispecific antibody with granulocyte-colony-stimulating factor in patients with metastatic breast cancer that overexpresses HER2/neu

Abstract: A phase I study of escalating doses of humanized bispecific antibody (bsAb) MDX-H210 with granulocyte-colony-stimulating factor (G-CSF) was conducted in patients with metastatic breast cancer that overexpressed HER2/neu. The main objectives of the study were to define the maximal tolerated dose (MTD) of MDX-H210 when combined with G-CSF, to measure the pharmacokinetics of MDX-H210 when administered with G-CSF, and to determine the toxicity, biological effects and possible therapeutic effect of MDX-H210 with G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Furthermore, G-CSF might contribute to an enhanced antiinflammatory cytokine response (Hartung et al, 1995). Concomitant administration of MDX-H210 and G-CSF seems to be safe in our study as well as in a multidose trial with MDX-H210 (Pullarkat et al, 1999). Interestingly, the side effects in our study were similar to other MDX-H210 studies, with other cytokines such as IFN-g or GM-CSF (Posey et al, 1999;Lewis et al, 2001).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, G-CSF might contribute to an enhanced antiinflammatory cytokine response (Hartung et al, 1995). Concomitant administration of MDX-H210 and G-CSF seems to be safe in our study as well as in a multidose trial with MDX-H210 (Pullarkat et al, 1999). Interestingly, the side effects in our study were similar to other MDX-H210 studies, with other cytokines such as IFN-g or GM-CSF (Posey et al, 1999;Lewis et al, 2001).…”
Section: Discussionsupporting
confidence: 74%
“…Strikingly less side effects were noted in these patients. This desensitisation phenomenon was also reported in other clinical trials with BsAb or mAb (Maloney et al, 1997;Dillman, 1999;Posey et al, 1999;Pullarkat et al, 1999).…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, stimulation of neutrophils with G-CSF (or IFN-␥) induces expression of the high affinity Fc␥RI (CD64), which represents the predominant cytotoxic Fc␥R on neutrophils (16). These data stimulated the evaluation of a combined therapy of G-CSF and Fc␥RI-specific BsAb in a number of clinical trials (17)(18)(19). These trials, however, only showed limited therapeutic effects, indicating that improvement of neutrophil-mediated Ab therapy is required.…”
mentioning
confidence: 99%
“…Targeting of tumors to Fc␥RI with bispecific mAbs 1 can facilitate tumor killing via Fc␥RI-expressing macrophages, and therapeutic humanized bispecific reagents targeting human Fc␥RIa are currently in clinical trials (13)(14)(15)(16)(17)(18)(19). Bispecific mAb-based antigen targeting to Fc␥RI can also enhance antigen presentation by dendritic cells with clear applications to enhanced immunization strategies (20).…”
mentioning
confidence: 99%